Sublobar resection without staging and lymphadenectomy for ≤2 cm Non-Small Cell Lung Cancer is no adequate therapy. (September 2022) - Schlachtenberger, Georg; Doerr, Fabian; Menghesha, Hruy; Hagmeyer, Lars; Bennink, Gerardus; Gaisendrees, Christopher; Wahlers, Thorsten; Hekmat, Khosro; Heldwein, Matthias B.
Abstract: Objective: Sublobar resection is frequently performed for Non-Small Cell Lung Cancer (NSCLC) patients with ≤2 cm nodules. Frequently, both proper staging and radical lymphadenectomy are omitted in these operations. Therefore, we decided to evaluate the number of lymph node metastases and the number of postoperative nodal upstaging in patients undergoing pulmonary resection due to NSCLC with tumors ≤2 cm at our institution. Methods: Nodal upstaging, lymphangiosis- (L1), and hemangiosis carcinomatosa (V1) were analyzed. pN0 patients were compared to patients with postoperative nodal upstaging. One-, three, and five-year survival rates were measured. Survival was also assessed by the Kaplan-Meier method. Results: 747 patients underwent surgery for NSCLC at our institution between 2012 and 2020. We retrospectively reviewed data of 236 NSCLC patients with ≤2 cm tumors. The mean tumor size was 1.4 cm ± 0.39 in our cohort. Of our patients, 14% showed a cT1a tumor, and 86% of patients cT1b. 24.0 ± 12.3 lymph nodes were dissected and analyzed per patient, and 0.7 ± 2.0 of those were affected. Of our patients, 16.1% showed L1 affection, and 7.6% a V1 affection. Lymph node involvement was diagnosed in 11(4.7%) patients preoperatively. 39(16.5%) patients were upstaged due to lymph node involvement postoperatively (p < 0.001). Upstaged patients showed significantly worse 3- (upstaged: 60.6% vs. pN0: 83.2%; p = 0.01) and 5-year (upstages: 38% vs. pN0 71.5%; p = 0.02) survival rates. Conclusion: 16.5% of patients with ≤2 cm NSCLC were nodal upstaged postoperatively. These results underline that lymphadenectomy and proper staging are crucial for NSCLC patients irrespective of the tumor size and the surgical approach. Highlights: Sublobar resection is a frequently performed for NSCLC patients with <2cm nodules. Many studies about sublobar resection do not perform guideline-based staging and little lymphadenectomy is performed. Of our patients with <2cm NSCLC 16.5% were nodal upstaged postoperatively. Of nodal upstaged patients 16.1% showed Lymphangiosis carcinomatosa (L1) and 7.5% showed L1 without lymph node affection. Preoperative staging and surgical management of NSCLC <2 cm should always follow current guidelines.